Biomarkers of ocular surface disease using impression cytology. (December 2017) - Hagan, Suzanne
Impression cytology (IC) is a technique which permits the retrieval of the outermost layer of ocular surface cells via the use of various types of filters. It is a minimally invasive method of evaluating human conjunctival epithelial cell morphology in the diagnosis of dry eye disease, a common and distressing disorder associated with ageing, contact lens wear, autoimmune disorders and refractive (LASIK) surgery. IC may also be utilized in the diagnosis of other ocular diseases, such as keratoconus and thyroid orbitopathy. More recently, IC has been utilized for the subsequent investigation of gene and protein expression of conjunctival cells in order to identify novel diagnostic biomarkers and to further our understanding of the mechanisms underlying ocular surface disease. This review will therefore examine the literature concerning the role of IC in identifying cellular markers of eye disease, systemic diseases with ocular involvement and potential novel therapeutic targets.